2020
DOI: 10.3390/ijms21072277
|View full text |Cite
|
Sign up to set email alerts
|

At the Crossroads of the Adipocyte and Osteoclast Differentiation Programs: Future Therapeutic Perspectives

Abstract: The coordinated development and function of bone-forming (osteoblasts) and bone-resorbing (osteoclasts) cells is critical for the maintenance of skeletal integrity and calcium homeostasis. An enhanced adipogenic versus osteogenic potential of bone marrow mesenchymal stem cells (MSCs) has been linked to bone loss associated with diseases such as diabetes mellitus, as well as aging and postmenopause. In addition to an inherent decrease in bone formation due to reduced osteoblast numbers, recent experimental evid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
51
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(51 citation statements)
references
References 88 publications
0
51
0
Order By: Relevance
“…In addition to osteoblasts, MSCs are also able to differentiate into adipocytes within bone marrow microenvironment. Increasing evidence suggests that the differentiation of MSCs into adipocytes or osteoblasts is competitively balanced (Li et al, 2016), and this delicate balance is important for the maintenance of bone homeostasis (Hu et al, 2018b;Muruganandan et al, 2020). Dysregulation of osteo-adipogenic differentiation balance of MSCs contributes to development of bone diseases, such as osteoporosis, which manifests typically as a lineage shift toward adipocytes instead of osteoblasts in MSCs (Qi et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…In addition to osteoblasts, MSCs are also able to differentiate into adipocytes within bone marrow microenvironment. Increasing evidence suggests that the differentiation of MSCs into adipocytes or osteoblasts is competitively balanced (Li et al, 2016), and this delicate balance is important for the maintenance of bone homeostasis (Hu et al, 2018b;Muruganandan et al, 2020). Dysregulation of osteo-adipogenic differentiation balance of MSCs contributes to development of bone diseases, such as osteoporosis, which manifests typically as a lineage shift toward adipocytes instead of osteoblasts in MSCs (Qi et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Bone marrow adipogenesis plays a critical role in bone loss associated with aging as well as diseases such as diabetes mellitus. The differentiation of adipocytes derived from MSC in bone marrow competes with osteoblastogenesis by its nature of lineage allocation while the mature adipocytes express RANKL and promote osteoclastogenesis [ 83 , 84 ]. Notably, among the adipogenic transcription factors, including CCAAT/enhancer binding protein alpha (C/EBPα), C/EBPβ, and peroxisome proliferator-associated receptor gamma (PPARγ), PPARγ is considered as a master factor for osteoclast differentiation from HSCs [ 85 ].…”
Section: Molecular Mechanism Of Bone Remodeling and Osteoporosismentioning
confidence: 99%
“…Furthermore, chemerin/CMKLR1 signaling induces expression of NFATc1 in HSCs, a key transcription factor for osteoclast differentiation, demonstrating that chemerin may potentiate bone loss in disease states [ 88 ]. Other adipokines such as visfatin and resistin represented similar activity, although the role of visfatin in bone remodeling is controversial [ 83 ]. Collectively, bone formation is regulated by the cell-to-cell contact involving RANK-RANKL in normal condition, however, adipocytes as well as adipokines can play critical roles in bone-loss-associated diseases.…”
Section: Molecular Mechanism Of Bone Remodeling and Osteoporosismentioning
confidence: 99%
“…RANKL induces osteoblasts to differentiate into osteoclasts and initiates osteolysis. 43 Hydroxyapatite (HA) is exposed on the surface of the dissolved bone, and this structure promotes tumor cell immobilization on the bone surface via αVβ3. 44 Bongjun Kim et al confirmed that acetylated RUNX2 induces RANKL expression, and protein acetylation was attributed to the fact that integrin αVβ3 mediates CCN2-stimulated acetylation and stabilization of RUNX2 in highly bonemetastatic cancer cells ( Figure 1).…”
Section: Dovepressmentioning
confidence: 99%